THE EMBODIMENT OF THE PHILOSOPHY OF ARTISTIC THINKING IN THE METAPHORIC OF THE NOVEL OF CHINGIZ AYTMATOV “AND A MORE THAN A CENTURY Lasts DAY” (Scientific journal of the Fergana State University, 2023)
This article discusses ChingizAitmatov's artistic mastery in creating a metaphorical model of the world. Using the example of the novel “And the Day Lasts a Century”, the originality of the writer's metaphor is analyzed.